Law and Economic Performance in the Roman World
1 online resource.
Keywords: Were legal systems in the Roman empire conducive to economic growth and development? Were legal rules and procedure changed in response to economic needs? This book offers detailed studies to provide some answers to these basic questions. This book offers critical analyses of the dynamic relation between legal regulations, institutions and economic performance in the Roman world. It studies how law and legal thought affected economic development, and vice versa. Inspired by New Institutional Economics scholars the past decades used ancient law to explain economic growth. There was, however, no natural selection process directing legal changes towards macro-economic efficiency. Ancient rulers and jurists modified institutions to serve or safeguard particular interests—political, social, or economic. Nevertheless both economic performance and legal scholarship peaked at unprecedented levels. These were momentous historical developments. How were they related?